PENGARUH SELF ASSESSMENT SYSTEM, PEMERIKSAAN PAJAK, DAN PENAGIHAN PAJAK PADA PENERIMAAN PAJAK PERTAMBAHAN NILAI (PPN) - Ivon Trisnayanti, Ida Ayu; Jati, I Ketut (E-Jurnal Akuntansi; Vol 13 No 1 (2015), 2015)
The increase in tax revenues in Indonesia related to the application of the Self Assessment system . Application of self assessment system causing tax arrears . To overcome these problems, carried out inspection and tax collection is a series of actions in order to pay off the tax debt underwriter taxes and costs of tax collection by the tax authorities in order to increase tax revenues . The purpose of this study was to determine the effect of the application of the self -assessment system , tax audits and tax collection at the reception of Value Added Tax on KPP North Badung . The data analysis technique used is multiple linear regression . Data collection methods used were interviews and documentation . Based on the results of analysis show that the self -assessment system , tax audits and tax collection impact on PPN receipts.
Keywords: Self Assessment System , Tax Audit , Tax Billing , Value Added Tax